What Else Can CD39 Tell Us? - Zhao, Hai; Bo, Cong; Kang, Yan; Li, Hong (Frontiers in Immunology, 2017)
As the rate-limiting enzyme in ATP/ADP-CD39-AMP-CD73-adenosine pathway，CD39 would be a novel checkpoint inhibitor target in preventing adenosine-triggered immune suppressive effect. In addition, CD39hi Tregs but not CD25hi Tregs exhibit sustained Foxp3 levels and functional abilities, indicating it may be a new specific marker of Tregs. Similiary，inhibition of CD39 enzymatic function at the surface of tumor cells alleviates their immunosuppressive activity. But far from conclusive，present research revealed that CD39 also dephosphorylate and thus inactivates self- and pathogen-associated phosphoantigens of Vγ9Vδ2 T cells which may be the most promising subpopulation for cellular vaccine. It is also tightly related to Th17 cells and can be partly used as Th17 cells marker. In this review, we sum up present research of CD39 ectoenzyme and provide insights into its clinical application.